Invasive aspergillosis in critically ill patients with diabetes mellitus: a systematic review and meta-analysis - Yuhua Liu; Zhaopei Zhang; Liang Zhou; Tianlai Lin; Rong Zhang; Manshu Li; Sihao Chen; Xiaoqing Liu; Xuesong Liu (BMC Infectious Diseases)
Abstract Background In the intensive care unit (ICU), invasive aspergillosis (IA) has a poor prognosis. Some studies report a positive association between diabetes mellitus (DM) and IA in critically ill patients, but the relationship between DM and IA in the ICU remains controversial. We aimed to clarify the relationship between DM and IA among patients in the ICU in a systematic review and meta-analysis. Methods We retrieved all reports published in PubMed, EMBASE, and the Cochrane Library databases before July 12, 2023. We calculated odds ratios (ORs) and 95% confidence intervals (CIs) to evaluate the relationship between DM and IA. Subgroup analyses were conducted to further analyze sources of heterogeneity. Heterogeneity was evaluated using the Cochran’s Q test and I2 statistic. Additionally, we evaluated publication bias using funnel plots, Egger’s test, and Begg’s test. Finally, sensitivity analysis was conducted to evaluate the robustness of the results. Results Twenty studies with 6155 participants were included in this meta-analysis. We found a positive association between DM and IA among patients in the ICU (OR = 1.18, 95% CI:1.01 to 1.39; p = 0.04). The heterogeneity was not significant (I² = 5%; p = 0.39) and publication bias was not significant (Egger’s test: p = 0.654; Begg’s test: p = 0.417). The results of sensitivity analysis supported a stable association between DM and IA. Subgroup analysis indicated that patients’ comorbidities might be a potential source of heterogeneity. Additionally, patients with DM had a significantly higher risk of COVID-19-associated pulmonary aspergillosis (CAPA) than those without DM (OR = 1.40, 95% CI: 1.15 to 1.70; p < 0.001). The heterogeneity was not significant (I² = 0%; p = 0.91). In the subgroup with influenza, the OR of the relationship between DM and IA was 0.81 (95% CI: 0.54, 1.23; p = 0.32; heterogeneity: p = 0.36; I² = 8%). Conclusions Patients with DM in the ICU showed a higher risk of developing IA than patients in the ICU without DM. DM was a significant risk factor for IA, with the highest risk observed in critically ill patients diagnosed with CAPA.